Parking study at Klinik Kesihatan Bandar Kuantan - Norhamiza, Rossli (2015)
Parking facility can be considered as part of planning requirement that can affect development scheme as a whole. Traffic conditions have tended to deteriorate and the searching time for parking space substantially increased. The increase of population, paralel with the increasing of road users lead to parking concerns, especially in Kuantan, Pahang. The study is to evaluate the car park at Klinik Kesihatan Bandar Kuantan, Pahang and to propose measure to improve the current situation based on parking demand. In case study, the methodology consists of three stage which is data collectin, data analysis and recommendation. Data analysis was done to obtain the actual rate of demands for parking space in these area compared to the availability of existing parking space. The results of the study was found that parking space here insufficient is to cater the for the user in the study area. Parking parameters methodology deals, in detail, with the data collection required for the evaluation process. The parking parameters of the condition of parking include parking durations, parking occupancy, Percentage of parking turnover, parking accumulation. A few recommendation will be suggested based on the results. The amount of data was collected and analyzed to show the parking situation. The most accurate method that used in this study is license plate survey method.